18F-FDG PET/CT findings in nevoid basal cell carcinoma syndrome: a systematic review and a new case report - Jing Zhang; Yonghong Zhang; Yumeng Jiang; Aodi Xu; Yanli Wang (BMC, 2024)
Abstract Background To demonstrate and analyze the 18F-FDG positron emission tomography/computed tomography (PET/CT) findings in this rare nevoid basal cell carcinoma syndrome (NBCCS). Case presentation A 71-year-old woman with the left invasive breast cancer was treated with hormone therapy for six months and underwent the 18F-FDG PET/CT examination for efficacy evaluation. 18F-FDG PET/CT revealed the improvement after treatment and other unexpected findings, including multiple nodules on the skin with 18F-FDG uptake, bone expansion of cystic lesions in the bilateral ribs, ectopic calcifications and dilated right ureter. She had no known family history. Then, the patient underwent surgical excision of the all skin nodules and the postoperative pathology were multiple basal cell carcinomas. Finally, the comprehensive diagnosis of NBCCS was made. The patient was still in follow-up. Additionally, we have summarized the reported cases (n = 3) with 18F-FDG PET/CT from the literature. Conclusions It is important to recognize this syndrome on 18F-FDG PET/CT because of different diagnoses and therapeutic consequences.